Literature Review: Factor Associated with Visual Inspection with Acetic Acid Screening among Women of Childbearing Age - Anani, Titi Nur Diah; Hasnawati; Sri wahyuni; Yasinta Dwi Rakhmawati; Nila Febriana; Luvi Dian Afriyani (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Cervical cancer is a malignancy originating from the cervix. In Indonesia, the number of cervical cancer patients ranks second highest after breast cancer, with a high mortality rate. To reduce this mortality rate, early detection is performed on women of childbearing age using the Visual Inspection with Acetic Acid method. However, the participation rate for Visual Inspection with Acetic Acid testing remains low. The method used in this study is a Systematic Literature Review (SLR) derived from two databases: Google Scholar and Semantic Scholar. The selected articles were in English or Indonesian, accessible in full text, and published between 2020 and 2024. Out of 15 identified articles, 7 met the criteria. The results of this study show that four articles mention individual factors such as good knowledge, attitude, and motivation influence participation in Visual Inspection with Acetic Acid testing, while three articles mention that health service and social factors, specifically counseling and decision-making support, are also required for participation. The findings indicate that factors related to Visual Inspection with Acetic Acid testing include individual, social, and health service factors. Visual Inspection with Acetic Acid testing is influenced by interrelated multidimensional factors. Therefore, comprehensive interventions are needed through increased health education, strengthening family support (especially from husbands), and improving the access and quality of health services to increase the coverage of Visual Inspection with Acetic Acid testing among women of childbearing age.